2021
DOI: 10.1021/acsami.1c00934
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate-Instructed Self-Assembly Selectively Inhibits Cancer Cell Migration

Abstract: Heparan sulfate (HS) has important emerging roles in oncogenesis, which represents potential therapeutic strategies for human cancers. However, due to the complexity of the HS signaling network, HS-targeted synthetic cancer therapeutics has never been successfully devised. To conquer the challenge, we developed HS-instructed self-assembling peptides by decorating the "Cardin−Weintraub" sequence with aromatic amino acids. The HS-binding interactions induce localized accumulation of synthetic peptides triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…(B3) TEM images of FFFFF-KRSR in the absence or presence of heparin. (B4) Wound-healing assay of co-cultured PANC-1-GFP/HS-5 cells upon the treatment of FFFFF-KRSR for 32 h. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Heparan Sulfate-targeted Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…(B3) TEM images of FFFFF-KRSR in the absence or presence of heparin. (B4) Wound-healing assay of co-cultured PANC-1-GFP/HS-5 cells upon the treatment of FFFFF-KRSR for 32 h. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Heparan Sulfate-targeted Self-assemblymentioning
confidence: 99%
“…As elucidated in Figure B, a well-designed peptide that selectively binds to HS will facilitate a localized accumulation triggering peptide assembly in the vicinity of HSPGs. The formed nanobiointerface on the plasma membrane hinders the interaction between HB-EGF and HSPG, inhibiting cancer cell migration . Three cationic peptide sequences including Phe-His-Arg-Arg-Ile-Lys-Ala (FHRRIKA), Lys-Arg-Ser-Arg (KRSR), and Leu-Arg-Lys-Lys-Leu-Gly-Lys-Ala (LRKKLGKA) that contain multiple lysine/arginine residues with the reported heparin-binding function were selected as HS-binding motifs.…”
Section: Heparan Sulfate-targeted Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ]. Recently, a study showed that heparan sulfate (HS)-instructed self-assembled peptides hinder the interaction between heparin-binding EGF-like growth factor (HB-EGF) and heparan sulfate proteoglycans (HSPG), thus inhibiting cancer cell migration [ 38 ]. it is therefore an effective way to inhibit the metastasis of malignant tumors and inspires researchers to explore therapeutics by using the self-assembly of small molecules.…”
Section: Self-assembly Of Small Organic Molecules In Theranosticsmentioning
confidence: 99%
“…HS has emerging roles in oncogenesis of potential therapeutic value for human cancers as part of a complex HS signalling network [254]. Cell-surface HSPGs of the Sdc and Gpc families have key roles in the regulation of cell behaviour, cell signalling, and cell matrix interactions in normal and pathological tissues [255][256][257].…”
Section: Potential Of Hs As a Therapeutic Target In Cancermentioning
confidence: 99%